Experimental comparison between speech transmission index (STI) and mean opinion scores (MOS) in rooms - Brachmanski, Stefan (Archives of Acoustics, 2006)
Two methods for assessment of speech quality in rooms were compared: the speech transmission index (STI) and mean opinion scores (MOS). Subjective and objective measurements were carried out in two rooms for different signal to noise ratio within a range from −15 dBA to +15 dBA. The obtained results are shown as a curve describing a relation between a MOS, STI and signal to noise ratio (S/N).